Slow Deep Breathing for Acute Post-Appendectomy Pain: A Gate Control Theory-Based Nursing Care Study - Jihan Yafi Dzakiyyah; Erik Kusuma; Eko Prasetya Widianto; Suhendra Agung Wibowo; Yenny Perwitosari; Yahya Tfeil (Inovasi Lokal, 2026)
Acute pain is one of the most consistent complications after appendectomy and, when left poorly controlled, delays mobilization, disrupts rest, and slows recovery. Slow deep breathing (SDB) is listed among the independent, non-pharmacological interventions in the Indonesian Nursing Intervention Standards, yet detailed, session-by-session accounts of how the technique is delivered at the bedside and how patients respond across successive post-operative days remain scarce in the nursing literature. This study described the nursing care process for a post-appendectomy patient with acute pain and evaluated within-subject changes in pain intensity and physiological indicators before and after three days of SDB therapy at Bangil Regional General Hospital (RSUD Bangil), Indonesia. A quasi-experimental, one-group pre-test post-test case design, embedded in the nursing process and reported in line with single-case reporting conventions, was used. SDB was delivered once daily for three consecutive days: inhalation through the nose for four seconds, breath-holding for two seconds, and exhalation through pursed lips for eight seconds, repeated across three cycles per session. Pain was scored with the Numeric Rating Scale (NRS) before and after each session. Pain intensity declined from severe (NRS 7) at baseline to mild (NRS 3) after the third session, accompanied by a drop in pulse rate from 104 to 87 beats per minute and the resolution of grimacing, restlessness, and protective behavior. SDB is a feasible, low-cost, nurse-initiated intervention that surgical wards can integrate into routine post-appendectomy pain management protocols alongside pharmacological treatment.